The introduction of performance related pay in the British Civil Service (1982-88): a cultural perspective - Keraudran Philippe
Since 1979 an attempt to modernize the state and restore its capacity as a central policy actor, the British government has kept the reform of the civil service as one of its political priorities. The back-ground of this reform is the acute and lasting economic crising since 1960 and which has often been termed the British decline. To achieve this Performance Related Pay was adopted by the reformer through two experimental schemes between 1982 and 1988. But the scheme failed totally. But it casts light on two plansible weakness in the process of induced organizational change: the first weakness is structural and the secondly weakness in apparently more behavioural.
Keywords: Civil Service -- Salaries etc. -- United Kingdom